TRANSFORMATION OF THE FUNCTIONING OF THE TOURISM SPHERE OF UKRAINE UNDER THE CONDITIONS OF THE MARITAL STATE AND EXPECTED DIRECTIONS OF ITS DEVELOPMENT IN THE POST-WAR PERIOD - SHEVCHUK, Lyubov; FEDORYSHYNA, Larysa; SHEVCHUK, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to outline the range of problems associated with the functioning of the tourism sphere of Ukraine in the conditions of martial law, and to determine promising directions for its development in the post-war period. The following research methods are used to achieve such purpose: theoretical synthesis, analysis, abstract and logical - to identify problems of the functioning of the tourism sphere of Ukraine; survey - to reveal the opinions of the respondents regarding the state and possible prospects for the development of tourism in Ukraine; graphic - for a visual presentation of survey results. The article is devoted to topical issues of organizing tourist flows under martial law. Economic losses in the field of tourism as a result of the war unleashed by Russia on the territory of Ukraine are outlined. The emergence of new types of tourism in the conditions of war has been proven. An author’s study was conducted on how military actions in Ukraine in 2022 affected the tourism sector. It was established that the majority of respondents consider rest during the war to be permissible (as a result - support of domestic tourism entities, improvement of the psycho-emotional state of the population, increase of the working capacity of the population, etc.); tourism will develop intensively after the victory of Ukraine, as our country will become a popular location for foreign tourists; and domestic tourism will become the most popular. The obtained survey results are highly representative and allow for a reliable analysis of public attitudes of the population regarding the need for rest during the war in Ukraine, the positive role of the tourism sector on both the social and economic development of Ukraine, and the restoration of the psycho-emotional state of a person during the war. In addition, attention is focused on the need to ensure the safety of tourists when organizing trips, and possible directions for the activation of tourism in the future are outlined. The war made adjustments to the development of tourism, which was already "going through" difficult times due to the COVID-19 pandemic, because the number of tourists decreased significantly, logistical problems arose with the organization of tourist trips, and part of the domestic tourist routes became dangerous, and in some places impossible to carry out. However, the tourism sector has significant potential, the use of which will contribute to the replenishment of community budgets, the restoration and preservation of people’s physical and mental health.